Restoration of Impaired Endothelial Myocyte Enhancer Factor 2 Function Rescues Pulmonary Arterial Hypertension. Issue 2 (13th January 2015) - Kim, Jongmin; Hwangbo, Cheol; Hu, Xiaoyue; Kang, Yujung; Papangeli, Irinna; Mehrotra, Devi; Park, Hyekyung; Ju, Hyekyung; McLean, Danielle L.; Comhair, Suzy A.; Erzurum, Serpil C.; Chun, Hyung J.
<x xml:space="preserve">Abstract</x> Background— Pulmonary arterial hypertension (PAH) is a progressive disease of the pulmonary arterioles, characterized by increased pulmonary arterial pressure and right ventricular failure. The cause of PAH is complex, but aberrant proliferation of the pulmonary artery endothelial cells (PAECs) and pulmonary artery smooth muscle cells is thought to play an important role in its pathogenesis. Understanding the mechanisms of transcriptional gene regulation involved in pulmonary vascular homeostasis can provide key insights into potential therapeutic strategies. Methods and Results— We demonstrate that the activity of the transcription factor myocyte enhancer factor 2 (MEF2) is significantly impaired in the PAECs derived from subjects with PAH. We identified MEF2 as the key cis-acting factor that regulates expression of a number of transcriptional targets involved in pulmonary vascular homeostasis, including microRNAs 424 and 503, connexins 37, and 40, and Krűppel Like Factors 2 and 4, which were found to be significantly decreased in PAH PAECs. The impaired MEF2 activity in PAH PAECs was mediated by excess nuclear accumulation of 2 class IIa histone deacetylases (HDACs) that inhibit its function, namely HDAC4 and HDAC5. Selective, pharmacological inhibition of class IIa HDACs led to restoration of MEF2 activity in PAECs, as demonstrated by increased expression of its transcriptional targets, decreased cell migration and proliferation, and rescue of experimental pulmonary hypertension models. Conclusions— Our results demonstrate that strategies to augment MEF2 activity hold potential therapeutic value in PAH. Moreover, we identify selective HDAC IIa inhibition as a viable alternative approach to avoid the potential adverse effects of broad spectrum HDAC inhibition in PAH.